2010
DOI: 10.1002/syn.20792
|View full text |Cite
|
Sign up to set email alerts
|

Rapid phasic activity of ventral pallidal neurons during cocaine self‐administration

Abstract: Little is known regarding the involvement of the ventral pallidum (VP) in cocaine-seeking behavior, in contrast with considerable documentation of the involvement of its major afferent, the nucleus accumbens, over the past thirty years utilizing electrophysiology, lesion, inactivation, molecular, imaging, and other approaches. The VP is neuroanatomically positioned to integrate signals projected from the nucleus accumbens, basolateral amygdala, and ventral tegmental area. In turn, VP projects to thalamoprefron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…An expectation from that reciprocal inhibition view would be that excitatory peaks of VP firing observed here might have corresponded to inhibitory pauses of NAc neurons, which have been suggested to signal reward (20,24,88,89). However, simultaneous excitations in NAc and VP (or simultaneous inhibitions) may also be possible (29,37,62,87,90), perhaps enabled by corelease of peptides such as dynorphin, enkephalin, or substance P to modulate the impact of GABA on postsynaptic neurons (5,6,32,87). Additionally, neurons of the NAc hotspot in the rostrodorsal medial shell may not project directly to neurons in the posterior VP hotspot recorded here but rather, to a more anterior site in VP and to lateral hypothalamus (7) from where interneurons might convey signals to posterior VP to contribute to functional interactions (37).…”
Section: Reward Component Separation By Population Segregation and Fimentioning
confidence: 73%
See 1 more Smart Citation
“…An expectation from that reciprocal inhibition view would be that excitatory peaks of VP firing observed here might have corresponded to inhibitory pauses of NAc neurons, which have been suggested to signal reward (20,24,88,89). However, simultaneous excitations in NAc and VP (or simultaneous inhibitions) may also be possible (29,37,62,87,90), perhaps enabled by corelease of peptides such as dynorphin, enkephalin, or substance P to modulate the impact of GABA on postsynaptic neurons (5,6,32,87). Additionally, neurons of the NAc hotspot in the rostrodorsal medial shell may not project directly to neurons in the posterior VP hotspot recorded here but rather, to a more anterior site in VP and to lateral hypothalamus (7) from where interneurons might convey signals to posterior VP to contribute to functional interactions (37).…”
Section: Reward Component Separation By Population Segregation and Fimentioning
confidence: 73%
“…Food, sex, drugs, winning money, and other rewards or predictive cues all activate these pathways in humans and other animals (11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Recent evidence indicates a surprising multiplicity of control systems within the NAc and VP, including multiple parallel and segregated loops that carry point to point signals through restricted subregions of prefrontal cortex-NAc-VP-thalamus and back again (7).…”
mentioning
confidence: 99%
“…Thus it is likely, but unexamined, that similar firing patterns exist in NAcc and VP neurons during cocaine self-administration. We recently demonstrated that VP neurons exhibit rapid phasic changes in firing during the seconds surrounding the cocaine-reinforced lever press (Root et al, 2010), as have been extensively observed in the NAcc (Carelli et al, 1993; Ghitza et al, 2004). A separate firing pattern, the slow phasic firing pattern , occurs over the minutes between self-infusions of cocaine and is exhibited in approximately half of NAcc neurons (Peoples and West, 1996; Peoples et al 1998; Fabbricatore et al 2010).…”
Section: Introductionmentioning
confidence: 80%
“…It has been proposed that neuronal ensembles can provide a mechanistic framework for understanding the behavioural and motivational effects of drug-associated cues 15, 42, 43 . Indeed, over the past two decades, several studies combining drug self-administration procedures 44 with in vivo electrophysiology have provided correlative evidence for a role of neuronal ensembles in several brain areas (the nucleus accumbens, medial prefrontal cortex (mPFC), ventral pallidum and basolateral amygdala) in cue-induced drug seeking 4550 . There is also limited correlative evidence from studies that compared context-specific locomotor sensitization behaviour with double-labelling of c-fos mRNA and FosB protein (Box 1) in context-specific selection of neuronal ensembles in the nucleus accumbens 15 .…”
Section: Neuronal Ensembles In Addiction and Relapsementioning
confidence: 99%